Incisional hernia rate after ileostomy closure in lateral pararectal stoma versus transrectal stoma placement: follow‐up of the randomized PATRASTOM trial. (12th November 2019) - Seyfried, S.; Lucas, V.; Galata, C.; Reißfelder, C.; Weiß, C.; Kienle, P.; Hardt, J.
Abstract: Aim: Because damage to the rectus abdominis muscle during ileostomy placement and reversal might be a risk factor for the development of stoma‐site incisional hernia (SSIH), we hypothesized that positioning of the stoma lateral to the rectus abdominis muscle might prevent SSIH. Method: To investigate whether a lateral pararectal stoma position lowers the incidence of SSIH in comparison with a transrectal position, a follow‐up study of the PATRASTOM trial, which had randomized stoma placement (lateral pararectal versus transrectal), was conducted. All former participants were invited simultaneously for a follow‐up visit in September 2016, 2 years after database closure of the PATRASTOM trial. For patients who were not able to attend the follow‐up, the electronic chart as well as MRI/CT scans were reviewed with regard to the presence of SSIH. Results: Follow‐up – either clinical or radiological – was available for 47 of the 60 PATRASTOM participants. The median duration of follow‐up was 3.4 years (interquartile range 3.0–4.1 years). SSIH occurred in 3 of 23 patients (13.0%) in the lateral pararectal group compared with 7 of 24 patients (29.2%) in the transrectal group ( P = 0.287). Four of the 10 patients diagnosed with SSIH had already undergone or were scheduled for hernia repair. Of the patient and procedure characteristics which may have an impact on the development of incisional hernia none was a significant risk factor for SSIH. Conclusion: In the present follow‐up study, no difference in the incidence of SSIH was found between lateral pararectal and transrectal stoma construction in an elective setting.